STRENGTHENING OF DAYAKNESE YOUTH SOCIAL CAPITAL TO IMPROVE ECONOMIC RESILIENCE IN BORDER AREAS - Helena Anggraeni (Reni) Tjondro Sugianto (Department of Management - Institut Shanti Bhuana, 2019)
This study aims to explore the potential of the social capital of the Dayak tribe in the border area that can increase economic and ecological resilience in the area. Since ancient times Dayak tribes have lived by relying on natural resources around them. Now, after the era has become more modern and forests are dwindling, nature is no longer able to support their old way of life. They began to settle down, unfortunately still with a long mental spirit, which is dependent on nature. As a result, many people still live in poverty along with their poorer natural resources. For this reason, it is necessary to reform a mindset among young people as successors in order to survive without relying entirely on nature. This research was conducted through a qualitative approach with grounded methods. The contribution for the economic theory is a way for strengthening social capital of Dayak youth in increasing economic and ecological resilience in the border region.